McCune-Albright syndrome. - Sharma, M.; Narang, T.; Gautam, R. (European Journal of Pediatric Dermatology, 2013)
McCune-Albright syndrome has a prevalence of 1:30,000. Classically, the syndrome presents a triad of hypermelanic lesions, polyostotic fibrous dysplasia and endocrinopathy. The endocrinopathies associated with the syndrome includes precocious puberty, hyperthyroidism, hypophosphatemic rickets, acromegaly, hyperprolactinemia, Cushing’s syndrome, hyperparathyroidism and gynecomastia. The severe forms may be associated with hepatic, cardiac and gastrointestinal dys-function. Its early manifestations are already present in childhood and early diagnosis is important for prevent malfunctions, improve esthetics and self-esteem of the patient. The clinical polymorphism requires a treatment tailored to each individual patient. A periodic follow-up is needed for the possible endocrine disorders and for the early detection of any tumors in adults.